Effect of ceramic etching protocols on resin bond strength to a feldspar ceramic - Bottino, M. A. [UNESP]; Snellaert, A.; Bergoli, C. D.; Oezcan, M.; Bottino, M. C.; Valandro, L. F. (Operative Dentistry Inc, 2015)
This study sought to evaluate the resin micro-tensile bond strength (MTBS) stability of a leucite-reinforced ceramic after different ceramic etching protocols. The microtensile test had 40 ceramic blocks (5x5x6 mm) assigned to five groups (n=8), in accordance with the following surface etching protocols: NE nonetched (control); 9HF: hydrofluoric (HF) acid etching (9% HF)+wash/dry; 4HF: 4%HF+wash/dry; 5HF: 5%HF+wash/dry; and 5HF+N: 5%HF+neutralizer+wash/dry+ultrasonic-cleaning. Etched ceramic surfaces were treated with a silane agent. Next, resin cement blocks were built on the prepared ceramic surface and stored for 24 hours in distilled water at 37 degrees C. The specimens were then sectioned to obtain microtensile beams (32/block), which were randomly assigned to the following conditions, nonaged (immediate test) and aged (water storage for 150 days plus 12,000 thermal cycles), before the microtensile test. Bond strength data were submitted to one-way analysis of variance and Tukey test (alpha=0.05). Additional ceramic samples were subjected to the different ceramic etching protocols and evaluated using a scanning electron microscope (n=2) and atomic force microscopy (n=2). Aging led to a statistically significant decrease in the MTBS for all groups, except the untreated one (NE). Among the groups submitted to the same aging conditions, the untreated (NE) revealed inferior MTBS values compared to the 9HF and 4HF groups. The 5HF and 5HF+N groups had intermediate mean values, being statistically similar to the higher values presented by the 9HF and 4HF groups and to the lower value associated with the NE group. The neutralization procedure did not enhance the ceramic/resin cement bond strength. HF acid etching is a crucial step in resin/ceramic bonding.